Neuroethics in the Era of Teleneurology - Young, Michael J. (Seminars in Neurology, 2022)
The accelerating integration of telehealth technologies in neurology practice has transformed traditional interactions between neurologists and patients, allied clinicians and society. Despite the immense promise of these technologies to improve systems of neurological care, the infusion of telehealth technologies into neurology practice introduces a host of unique ethical challenges. Proactive consideration of the ethical dimensions of teleneurology and of the impact of these innovations on the field of neurology more generally can help to ensure responsible development and deployment across stages of implementation. Toward these ends, this article explores key ethical dimensions of teleneurology practice and policy, presents a normative framework for their consideration, and calls attention to underexplored questions ripe for further study at this evolving nexus of teleneurology and neuroethics. To promote successful and ethically resilient development of teleneurology across diverse contexts, clinicians, organizational leaders, and information technology specialists should work closely with neuroethicists with the common goal of identifying and rigorously assessing the trajectories and potential limits of teleneurology systems.
Keywords: teleneurology; neuroethics; telehealth; telemedicine; bioethics; disorders of consciousness